Engajamento moral nos videogames: o design de escolhas de Fallout: New Vegas - Cunha, Anya Schmidt (2024)
Video games, as an interactive medium, allow the system to respond directly to the player's actions. This characteristic provides a unique way to explore moral narratives by introducing agency, allowing decisions to lead to narrative developments. However, as a common feature in games is the presence of objectives, it’s possible that choices may lose some of their moral weight in favor of a strategic approach. Moral engagement is said to occur when the player makes decisions based on ethical principles. Moral engagement is directly related to the immersive process and the desire to act in the fictional world as a moral agent. This action takes place through choices: the game system presents a state and offers different possible actions; the player selects one of these actions, the game's state changes, and this change is communicated back to her. At each of these stages, there is a range of design decisions that influence the gaming experience. This research aims to explore the immersive process that leads to protagonization, analyze different approaches to the design of moral choices, and examine, through a case study of the game Fallout: New Vegas, how the structure of these choices can impact moral engagement